Transformasi Karakter Kristen dalam Perjanjian Baru: Kajian Teologis atas Buah Roh dan Etika Kasih - Refamati Gulo; Alexander Naulus Rupidara; Robert Patannang Borrong (JURNAL LUXNOS, 2025)
Character in the New Testament perspective is closely related to a person who has accepted Jesus as Lord and Savior. Character is the main concern of Jesus Christ and the apostles because it reflects the growth of faith and the ability to implement His teachings in daily life. Character formation creates a person who fears God, lives in harmony with God's love, and follows the rules taught by Jesus. People who fear God tend to have a ritualistic attitude, love the truth, and are firm in moral principles. In contrast, people who do not fear God exhibit the opposite attitude. Christian character affects not only the number of believers, but also the quality of life in accordance with God's word. Christians are expected to exert a positive influence through their faith and good character, bear witness to Christ through their actions, and encourage others to follow Jesus' example. This study aims to explain the importance of Christian character in the New Testament as a foundation for believers to be role models, both for unbelievers and for the Christian community. In addition, Christian character has an important role in cultivating the traits of Christ in daily life. This research uses a qualitative research method with a Christian theological and ethical study approach, namely to understand the meaning and interpretation of experiences, beliefs, and practices.